Green Walnut Husk Ameliorating the Adverse Effects Induced by High Fat Diet in Rats - Rozha, Sharif O; Hawraz, Farhad M; Harseen, Mahmud R; Hassan, Ali H; Rebin, Kanabi M; Dyary, Hiewa O; Lava, Muhammed S; Soz, Mazn M (The Iraqi Journal of Veterinary Medicine, 2021)
This study was designed to investigate the ameliorating effect of methanolic extract of green walnut husk (GWH) in hypercholesterolemic rats. A total of thirty male Albino Wistar rats (Rattus norvegicus domestica) were divided randomly into six equal groups. Group 1, negative control, fed on a standard rat diet whereas groups 2–6, hypercholesterolemic rats, fed a high-fat diet (1% cholesterol in a standard diet). Group 2, positive control, was left untreated, whereas the groups 3–5 treated orally with methanolic extract of GWH at 200, 400, and 800 mg/kg/day BW, respectively. Group 6, treatment control, received atorvastatin intraperitoneally at a dosage rate of 0.8 mg/kg/day. The treatment lasted for 84 days. Lipid profiles, biomarkers for liver and kidney functions, some hematological parameters, and liver histopathological assessment were performed. No significant variation was observed on lipid profile values after 42 days of GWH intake; while after 84 days, there was significant reduction (P<0.05) in cholesterol, LDL, and triglycerides and significant increase (P<0.05) in HDL. On day 42, the GWH intake revealed no ameliorating effect on ALT, AST, ALP, serum creatinine, and blood urea nitrogen (BUN); while on day 84, the GWH at 400 and 800 mg/kg BW reduced liver injury enzymes and serum creatinine levels but not the BUN. The GWH showed no significant effect on RBC, HGH, HCV, MCH, and MCHC counts; however, the WBCs count of all experimental groups showed significant (P<0.05) increase when compared to negative control. In comparison with other experimental groups, the 800 mg/kg GWH group and the treatment control group exhibited significant decrease (P<0.05) in HCT. The histopathological findings of the liver showed that the 800 mg/kg BW dosage rate of GWH was efficient in ameliorating the adverse tissue changes noticed in the positive control and other experimental groups. It can be inferred that GWH at dosage rate 200, 400, and 800 mg/kg BW have a potential antidyslipidemic effect in dose and period dependent manner. Further investigation to identify the safety of GWH for long standing using against hyperlipidemic patients is required.